Estudo e implementação de uma luminária de iluminação pública à base de LEDs - Maggi, Tiago (2013)
This work presents a study for the design and implementation of a LED Street light Luminaire. It shows the necessary characteristics for the proposed fixture replace the traditional models with High Pressure Sodium lamps (HPS), which are commonly used in Brazil. For this, it has been done a study and implementation of a LED fixture prototype that can replace a conventional fixture, keeping the photometric characteristics required by Brazilian standards. With this, is possible a significant reduction in the electrical power consumption by exploring the LED features such as high energy efficiency, long life, low luminous flux depreciation during the life and facility for light direction control. Here is presented an analysis of some traditional HPS lamps models to allow comparison of results of the prototype proposed. In this study is verified that the proposed LED fixture can reach similar levels of illuminance on the road that HPS modes, however using almost 50% of electric power.